Decarbonize Urban Heating System China Building Energy and Emission Yearbook 2023. (Springer Nature Singapore : Imprint: Springer, 2024)
This is an open access book. The double-carbon target has been one of the main motivations and goals for China's social and economic development. The building sector is one of the most important sectors to achieve energy saving and emission reduction. This publication thoroughly examines China's building energy use and carbon emissions with a focus on four categories, including their characteristics and the technologies needed to achieve zero carbon emissions. This year, the key issue is developing carbon-neutrality pathways for China's urban heating system. This report comprehensively discusses the current status and future forecast of heat demand in buildings and non-process industries, introduces the challenges facing the urban energy supply system in achieving carbon neutrality, and elucidates the low-carbon heating model based mainly on low-grade and low-carbon waste heat. Extensive survey and monitoring data and case studies are presented throughout the book. The discussion of technologies and policies has been the subject of extensive research and evidence for over a decade. The information, data, and policy recommendations are of relevance to a national and global audience working in the fields of energy, climate change, engineering, and building science.